2005
DOI: 10.1021/ja042711t
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Fragmentation of Transition Metal Nanoparticles in Ionic Liquids

Abstract: Stable Pd(0) and Rh(0) nanoparticles with small and narrow size distribution can be prepared from relative large and agglomerated transition-metal particles dispersed in 1-n-butyl-3methylimidazolium hexafluorophosphate ionic liquid by simple laser irradiation. The laser irradiation is a complementary method for the generation of stable metal colloids in ionic liquids and also for the regeneration of small-size nanoparticles that may result from their agglomeration after different applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 21 publications
2
93
0
Order By: Relevance
“…[29] Alternatively, in situ laser radiation may be used to induce the fragmentation of relatively large MNPs dispersed in ILs into smaller particles with a narrow size distribution. [30] The formation of the nanoparticles from methods 1) and 2) apparently follows the autocatalytic mechanism developed by Finke and co-workers [31,32] that basically involves two steps: nucleation and surface growth. In various cases these IL colloidal mixtures can be used directly as catalysts or they may be isolated and used as powders in solventless conditions (the substrates/products are per definition the solvent) or re-dispersed in the ILs (see below).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[29] Alternatively, in situ laser radiation may be used to induce the fragmentation of relatively large MNPs dispersed in ILs into smaller particles with a narrow size distribution. [30] The formation of the nanoparticles from methods 1) and 2) apparently follows the autocatalytic mechanism developed by Finke and co-workers [31,32] that basically involves two steps: nucleation and surface growth. In various cases these IL colloidal mixtures can be used directly as catalysts or they may be isolated and used as powders in solventless conditions (the substrates/products are per definition the solvent) or re-dispersed in the ILs (see below).…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, XPS spectra after sputtering displays mainly the M À M component at the 4f region, demonstrating that only the external surface metal atoms are bound to F and O. [24,26,30,33,35] Inasmuch as most of the 1,3-dialkylimidazolium ionic liquids have extremely low vapor pressure [36][37][38] and relatively high viscosity at room temperature, [39][40][41][42] in situ TEM [23,43] and XPS [44] -which require high vacuum-could be performed with the MNPs dispersed in ILs. [37] The size and shape determined by this TEM in situ technique are the same as that obtained with the isolated nanoparticles which were mixed with an epoxy resin distributed between two silicon wafer pieces.…”
Section: Introductionmentioning
confidence: 99%
“…At first glance, ILs do not seem to be suitable solvents for nanoparticles because of their high ionic strengths; however, many studies on nanomaterials in ILs have been reported. [149][150][151][152] We have clarified that colloidal materials (nanoparticles) in ILs are normally unstable and easily aggregate, forming gels due to the network formation of the nanoparticles. However, stable dispersions in ILs can be produced if there are IL-philic structures at the interfaces or strong interactions between the surface of the nanoparticles and either the cation or anion of the IL (Fig.…”
Section: Colloidal Stability In Ils and Materializationmentioning
confidence: 99%
“…Metal nanoparticles are easily prepared using the following methods: -controlled decomposition of organometallic compounds in the formal zero oxidation state such as [Pt 2 (dba) 3 ] (Scheeren et al, 2003), Ru (cod) (cot)] (Silveira et al, 2004) (Fonseca et al, 2003), and RuO 2 dispersed in ionic liquids; -simple transfer of the nanoparticles freshly prepared in water or "classical" organic solvents to the ionic liquids (Zhao et al, 2006). Alternatively, in situ laser radiation may be used to induce the fragmentation of relatively large nanoparticles dispersed in ionic liquids into smaller particles with a narrow size distribution (Gelesky et al, 2005).…”
Section: Synthesis Of Metal Nanoparticles In Ionic Liquidsmentioning
confidence: 99%
“…The Rh nanoparticles were prepared by simple hydrogen reduction of [Rh(cod)-µ-Cl] 2 (cod=1,5-cyclooctadiene) dispersed in 1-n-butyl-3-methylimidazolium hexafluorophosphate at 75 °C. After 60 minutes darkening of the solution was observed indicating the formation of Rh (0) nanoparticles (Gelesky et al, 2005). Stable ruthenium, rhodium, and iridium metal nanoparticles have been reproducibly obtained by facile, rapid, and energy-saving microwave irradiation under an argon atmosphere from their metal-carbonyl precursors [M (x)( CO) (y) ] in the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate (Redel et al, 2009;Vollmer et al, 2010).…”
Section: Ionic Liquid Assisted Of Metal Nanoparticles: Ir(0) and Rh(0)mentioning
confidence: 99%